2003
DOI: 10.1097/01.tp.0000065299.29900.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Superoxide Dismutase Genes Delivered With an Adenovirus on Graft Function After Transplantation of Fatty Livers in the Rat1

Abstract: This study demonstrates that cytosolic SOD represents the most effective isoform of SOD to protect transplanted livers from failure; this may be related to lowered NF-kappaB and JNK activities because of reduced oxygen-derived radical production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Experimental studies have previously shown that upregulation of HO-1 protects liver grafts against ischemia/reperfusion injury and improves graft survival (2,3,37-39). Especially, steatotic livers, which are highly sensitive to ischemic injury, seem effectively protected against this type of injury by induction of HO-1 (37,40). The inferior outcomes of livers with the unfavorable TT genotype (associated with a reduced HO-1 promoter activity) in the current study supports these previous findings.…”
Section: Ho-1 Polymorphisms and Outcome After Liver Transplantationsupporting
confidence: 82%
“…Experimental studies have previously shown that upregulation of HO-1 protects liver grafts against ischemia/reperfusion injury and improves graft survival (2,3,37-39). Especially, steatotic livers, which are highly sensitive to ischemic injury, seem effectively protected against this type of injury by induction of HO-1 (37,40). The inferior outcomes of livers with the unfavorable TT genotype (associated with a reduced HO-1 promoter activity) in the current study supports these previous findings.…”
Section: Ho-1 Polymorphisms and Outcome After Liver Transplantationsupporting
confidence: 82%
“…However, baseline levels of antioxidants were not measured between steatotic and lean livers but have been previously reported to be similar [111]. These results further confirm that steatotic livers have a predisposition for increased ROS production rather than lacking antioxidants.…”
Section: Troloxsupporting
confidence: 75%
“…However, our results obtained with the pharmacological modulation of MAPKs, are in line with those reported in a study in transplantation from steatotic liver grafts indicating that JNK activation might be harmful to hepatocytes after reperfusion. 54 In addition, under the conditions reported here, the levels of both p38 and JNK fell in both liver types following preconditioning. These apparently contradictory data on MAPKs in liver preconditioning have also been reported for the heart.…”
Section: 34mentioning
confidence: 80%